The potential of virtual natural environments: a critical analysis of a VR-based mindfulness approach - Marocco, Silvia; Vitale, Valeria; Grossi, Elena; Presaghi, Fabio; Talamo, Alessandra (Frontiers in Psychology, 2025)
The relationship between environmental factors and mental health is widely acknowledged in the field of Environmental Psychology, with nature-based therapies emerging as a promising approach for mental health treatment. In particular, nature has been recognized as a valuable complementary resource for mindfulness practice. At the same time, Virtual Reality (VR) provides innovative solutions to the challenges posed by conventional mindfulness practices, reducing external distractions and fostering an immersive, present-focused experience. This study explores the effects of a nature VR-based and a conventional mindfulness intervention on the mindfulness state (decentering and curiosity) and emotions (positive and negative), with the aim of determining whether virtual nature can enhance mindfulness practice. The findings indicate that both conventional and VR-based mindfulness interventions effectively enhanced decentering; however, only the VR-based intervention significantly reduced negative emotions, suggesting that virtual natural environments may play a role in emotional regulation, as supported by previous research. On the other hand, no significant changes were observed in terms of curiosity or positive emotions across both intervention types. Overall, this study contributes to the understanding of how nature-based therapies and immersive technologies can support mental health treatment, providing a foundation for future research on the potential synergy between VR, mindfulness, and natural environments.